2021
DOI: 10.1055/s-0041-1731767
|View full text |Cite
|
Sign up to set email alerts
|

Does Incisional Negative Pressure Wound Therapy Prevent Sternal Wound Infections?

Abstract: Background Incisional negative pressure wound therapy has been described as an effective method to prevent wound infections after open heart surgery in several publications. However, most studies have examined relatively small patient groups, only a few were randomized, and some have manufacturer-sponsorship. Most of the studies have utilized Prevena; there are only a few reports describing the PICO incisional negative pressure wound therapy system. Methods We conducted a prospective cohort study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 30 publications
2
19
1
Order By: Relevance
“…We speculate that the use of NPWT may be most effective for the prevention of deep SWI with a net benefit for the overall rates of any SWIs. This is confirmed by the results of most studies, with few exceptions [ 11 ]. A few recent studies [ 11 , 13 , 16 ] showed that there is a widespread use of this treatment, which suggest that clinicians are confident of a net benefit of NPWT, particularly in patients at highest risk of surgical site infection [ 11 , 13 ].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…We speculate that the use of NPWT may be most effective for the prevention of deep SWI with a net benefit for the overall rates of any SWIs. This is confirmed by the results of most studies, with few exceptions [ 11 ]. A few recent studies [ 11 , 13 , 16 ] showed that there is a widespread use of this treatment, which suggest that clinicians are confident of a net benefit of NPWT, particularly in patients at highest risk of surgical site infection [ 11 , 13 ].…”
Section: Discussionsupporting
confidence: 82%
“…This is confirmed by the results of most studies, with few exceptions [ 11 ]. A few recent studies [ 11 , 13 , 16 ] showed that there is a widespread use of this treatment, which suggest that clinicians are confident of a net benefit of NPWT, particularly in patients at highest risk of surgical site infection [ 11 , 13 ]. Since the risk of SWI is particularly increased after bilateral internal mammary artery grafting [ 21 ], a benefit with the preventative use of NPWT may be more evident in such high-risk patients.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations